Adverse events related to platelet-rich plasma therapy and future issues to be resolved - Anna Arita; Morikuni Tobita (Regenerative Therapy)
Platelet-rich plasma (PRP) is the portion of plasma with a platelet concentration above baseline that is recovered through centrifugation of autologous blood. PRP therapy is currently used for wound healing and pain relief in diverse medical fields. Although there have been recent reports of adverse events (AEs) possibly related to PRP treatment, the safety profile of PRP treatment remains unclear. Therefore, this review discusses the risks inherent in PRP therapy and the current issues by surveying reports on AEs associated with PRP treatment within different fields.PubMed was searched for research articles referring to AEs associated with PRP therapy from inception to January 2024. Literature survey revealed that PRP therapy may involve several AEs, including postoperative infections, blindness, inflammation, allergic reactions, and nodule development. The most commonly reported AE was postoperative infections. Since PRP therapy generally proceeds in the process of blood collection, manufacturing, and administration to patients, it is conjectured that PRP may have been contaminated with microorganisms at some point in this series of processes, leading to bacterial infection. Additionally, because PRP cannot be sterilized like pharmaceuticals, it is important to prevent microbial contamination during each PRP treatment process. However, the specific process that involves the risk of microbial contamination remains unclear. To take measures to prevent microbial contamination of PRP, it may be necessary to elucidate the risk factors for microbial contamination during PRP treatment. It may be important to elucidate the effectiveness and risks of PRP therapy as well as to establish a follow-up system after PRP treatment. Currently, most reports of AEs related to PRP therapy are case reports; therefore, the accumulation of high-quality evidence and detailed verification are necessary to determine the causal relationship between PRP therapy and each AE.